ANALYSIS OF STOPPING SIGHT DISTANCE FOR GEOMETRIC ELEMENTS FOR ROADS IN MATARAM-LEMBAR - Alit Karyawan, I Dewa Made; Widianty, Desi (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Traffic volume road section Mataram-Lembar dense enough, linking two vital objects, that the Port Lembar and Lombok International Airport, ideally have a good level of service. Research on these roads aims to determine the minimum stopping sight distance based on vehicle speed and sight distance are available as well as safety analysis based on the availability and sight distance needs. The method used is to perform data analysis of primary and secondary data for obtained stopping sight distance (SSD), include: SSD available in the field based on the analysis of the road measurement data, SSD minimum based on the speed in site and SSD based on the design speed. The results showed there are 4 corners that do not meet the elements of safety because of the stop sight distance available in the field is smaller than required at curve 2, curve 3, curve 4 and curve 5. Just curved bends 1 that meets the safety requirements. Sight distance is not appropriate is as follows: a) In the second bend 50-meter-Lembar Mataram direction and 75 meters towards Lembar-Mataram b) In the third bend 100 meters along the direction of Mataram-Lembar and 75 meters towards Lembar-Mataram.; c) In the fourth round the bend towards Mataram 75 meters and 75 meters-Lembar direction Lembar-Mataram.; d) In the fifth bend 125 meters along the direction of Mataram-Lembar and 100 meters towards Lembar-Mataram.